Bending performance and design of reinforced concrete ribbed bridge deck slabs retrofitted with steel-plate reinforcement - Jianshuai Liu; Shuai Tian; Tao Li (Journal of Asian Architecture and Building Engineering)
This study aimed to assess the bending performance and design of reinforced concrete ribbed bridge deck slabs with steel-plate reinforcement. Two reference members and three steel-plate reinforcements were designed for four-point bending loading tests, numerical simulations, and theoretical analyses. Steel-plate reinforcement improves the flexural load bearing capacity and stiffness of the bridge deck slab and effectively controls crack development, compared to old bridge reconstruction requirements. The bridge deck is best stressed when the bolt (M12 mm × 200 mm) spacing is 0.8 times the slab thickness. To prevent brittle damage to the bridge deck, a steel plate with a width of 160 mm and thickness of 10 mm should be used for strengthening. This aligns with engineering practice whereby the bolt shear capacity is used to assess the effectiveness of steel-plate reinforcement in bridge deck slabs. Bolt shear arrangement based on the slip effect and a sufficient increase in the diameter of the bolts at both ends of the steel plate are more appropriate for the bending effect of the bridge deck structure. The results provide a reference for the design of deck slab reinforcement for assembled ribbed bridges.